Synthesis of CuInSe2 nanopowders by microwave assisted solvothermal method. (8th January 2014) - Pulgarin–Agudelo, F.A.; Placidi, M.; Fairbrother, A.; Fontané, X.; Roca, V. Izquierdo; Sebastian, P.J.; Ramos, F.; Pina, B.; Pérez–Rodríguez, A.; Saucedo, E.
CuInSe2 (CISe) nanopowders were synthesised using the innovative microwave assisted solvothermal method. We studied the impact of the synthesis temperature as well as the precursor composition on the morphological, compositional, and structural properties of the nanopowders. We have found that for the synthesis of stoichiometric CISe particulates with chalcopyrite phase structure, temperatures equal to 230°C and In concentration in excess in the reaction solution with respect to Cu are required. At lower temperatures (200°C) and In excess, the presence of binary phases such as Cux Se and In2 Se3 is clearly detected indicating a inadequate In incorporation. At intermediate temperatures (215°C), CISe is mainly formed but preferentially with the Cu–Au polytype structure. The method presented here may be very interesting for the possible mass production of CISe nanopowders due to the facile temperature control, the fast reaction process, and the easy scalability.